Composition and diversity of culturable cyanobacteria in sediment samples from the upper layers of two tropical reservoirs dos embalses tropicales (2024)
ABSTRACT: Benthic cyanobacteria research in high mountain reservoirs remains limited, mainly due to their complexity and knowledge gaps that persist in relation to their ecology in tropical regions. This study aimed to explore the composition, diversity, and toxic potential of cyanobacterial in the upper sediment of two Colombian reservoirs. Our investigation involved multiple methodologies, such as germination experiments, that allowed us to assess the presence and viability of cyanobacteria in upper sediment samples, while the competitive ELISA assay allowed for the quantification of toxins within the cultures. The molecular analysis of Operational Taxonomic Units (OTUs) from subsamples of sediment cultures focused on evaluating cyanobacterial diversity and richness among prokaryotic phyla, and the Phylogenetic analysis of culturable cyanobacteria. Chlorophyll-a measurements confirmed the presence of viable populations in sediment cultures, while microscopic identification demonstrated the growth capacity of cyanobacteria from the orders Nostocales, Chroococcales, Oscillatoriales, and Synechococcales under controlled laboratory conditions. Despite low microcystin levels in culture, the prior detection of mcy genes in direct sediment samples suggests a possible toxic potential of cyanobacterial inhabiting the upper sediments. Community analysis, based on the OTUs abundance, revealed a notably diverse microbial community in both reservoir sediments, with a higher relative abundance of cyanobacteria compared to other prokaryotic phyla. These findings support the hypothesis that surface sediments play a fundamental role as a repository for cyanobacteria that may pose inherent risks to ecosystem health. In conclusion, this research underscores the necessity of further studies to achieve a holistic comprehension of benthic cyanobacteria dynamics in high-mountain tropical reservoirs.